1978
DOI: 10.1042/cs0540355
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Folate-Derived Pteridines in Rat Liver

Abstract: 1. It has previously been shown that folate polyglutamates in the rat are catabolized almost exclusively via cleavage of the C-9--N-10 bond, resulting in the formation of pteridines and p-aminobenzoylglutamate. The latter catabolite is rapidly excreted, appearing in the urine as acetamidobenzoylglutamate and is undetectable in rat liver. 2. The pteridines catabolites on the other hand are retained to a much greater extent by the liver, forming an ever-increasing proportion of the retained radioactive tracer. 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1979
1979
1979
1979

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…While working with a single patient they found diphenylhydantoin increased excretion of newly absorbed PteGlu but did not increase catabolism. How-ever, these workers used [2-14C]PteGlu which upon catabolism produces a labeled pteridine only, which has been found to be further metabolized to produce several different pteridines which are retained by the liver for prolonged periods (19). This retention may obscure the clear increase in the catabolic rate effected by diphenylhydantoin (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While working with a single patient they found diphenylhydantoin increased excretion of newly absorbed PteGlu but did not increase catabolism. How-ever, these workers used [2-14C]PteGlu which upon catabolism produces a labeled pteridine only, which has been found to be further metabolized to produce several different pteridines which are retained by the liver for prolonged periods (19). This retention may obscure the clear increase in the catabolic rate effected by diphenylhydantoin (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies in rats have shown that a tracer dose of high specific activity [3H]pteroylglutamate (PteGlu)1 becomes fully equilibrated into the tissue folate polyglutamate pools after periods of 2 or 3 d (17). With such a tracer dose to label the endogenous pools we have recently elucidated the mechanism of folate catabolism in the rat (18), and have shown that it proceeds via cleavage of the C9-N10 bond of the molecule to yield pteridines, which are retained by the liver and released slowly (19), and p-aminobenzoylglutamate (pABGlu), most of which is first acetylated to produce acetamidobenzoylglutamate (ApABGlu) and then rapidly excreted in the urine (18). In the 1st 3 d after administration of labeled PteGlu, i.e., during the equilibration of the tracer dose, a complex mixture of folate derivatives is found in the urine (18,(20)(21)(22)(23)(24)(25).…”
Section: Introductionmentioning
confidence: 99%